Impact of the Present-Day Climate Changes on the Natural Plague Foci Condition, Situated in the Territory of the Russian Federation and Other CIS Countries - N. V. Popov; V. E. Bezsmertny; A. I. Udovikov; A. A. Kuznetsov; A. A. Sludsky; A. N. Matrosov; T. V. Knyazeva; Yu. M. Fedorov; V. P. Popov; A. K. Grazhdanov; T. Z. Ayazbaev; S. A. Yakovlev; et al. (Проблемы особо опасных инфекций, 2013)
Climate changes determine dynamics of epizootic activity of natural plague foci in the XX and XXI centuries. Obvious shift to continentality in the Northern hemisphere can put an end to inter-epizootic period in lowland steppe and semi-desert natural foci of the Pre-Caucasian region, North and North-West Caspian Sea regions. Presently observed conjoined development of inter-epizootic periods in natural plague foci with different biocoenotic structure in the territory of Pre-Caspian Lowland gives the grounds for assuming the presence of a common cause preconditioning parasitic system depression in the region. One of the key elements of this phenomenon is a change of status of little souslik – formerly the main plague carrier in the region. Subsequent to the climate change the key role of plague carrier is more often played by non-hibernating rodent species nowadays. Thus a significant increase in epizootic potential of steppe natural plague foci in the territory of Kazakhstan and Central Asia is prognosticated. With the further temperature fall during wintertime, snow cover height increase and glacial area extension epizootic activity of the mountain and high mountain foci must drop off significantly. Alongside with this updated data on plague agent ecology, predetermining possibility of its existence in the soil biota, confirm the key role of climactic factors in the plague enzootic outbreak.